Analisis Pengaruh Citra Merek, Harga, Promosi Dan Kualitas Produk Terhadap Keputusan Pembelian Pada Sorum Rudi Mobil Malang (Studi Kasus Pada Konsumen Sorum Rudi Mobil Malang) - Ony Dzaky Abdillah; Rois Arifin; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis research was conducted at Sorum Rudi Mobil Malang in Pakis District, Malang Regency. This type of research used in this research is quantitative research. The purpose of this study was to determine and analyze the effect of brand image, price, promotion and product quality on purchasing decisions. The independent variables used are brand image, price, promotion and product quality, while the dependent variable is the purchase decision. The sample used in this study were 85 respondents who purchased a car at Sorum Rudi Mobil Malang. The data collection technique used a questionnaire. The analysis method used is validity test, reliability test, normality test, classical assumption test, hypothesis test, determination test with the help of SPSS software. The results of this study indicate that the variables of price, promotion and product quality have a positive and significant effect on purchasing decisions, but brand image has no effect on purchasing decisions.Keywords: purchasing decisions, brand image, price, promotion and product quality.